A convalescença como possibilidade de saúde para o corpo nos escritos de Nietzsche - Conceição, Gilmar Dias da (2015)
The objective of this dissertation paper in Masters is the study of the itinerary followed by Nietzsche in elaborating his perspective on the body, starting from the antecedents that determined its devaluation. In this journey, we shall be examining, among other points, the Nietzsche perspective on the human decadency process, with emphasis on what the above mentioned thinker understands by Physiology and the art of convalescence, and showing how it configures the process of human sickness both individually and collectively